PELATIHAN PEMBUATAN KONEKTOR MASKER DAN SOSIALISASI PEMANFAATAN SOSIAL MEDIA SEBAGAI MEDIA PENJUALAN - Suci Nurani; Rizal Fahlevi; Fajri Ryan Isnandar; Isfandayani Isfandayani (LPPM Universitas Islam 45, 2022)
The Covid pandemic has caused shortages of food, drinks and health items such as medicines and masks. From the use of these masks, there are opportunities that can increase household income, namely the manufacture of mask connectors which are usually used by hijab users. The method used in this community service is training. The results during the training were based on the participants' statements that the training was very useful for opening a small business using a small amount of capital.